F5 Social cognition in huntington's disease: evidence from a prospective study. (13th September 2016) - Unti, Elisa; Mazzucchi, Sonia; Palermo, Giovanni; Kiferle, Lorenzo; Pagni, Cristina; Tognoni, Gloria; Bonuccelli, Ubaldo; Ceravolo, Roberto
Abstract : Background: Impaired social behaviour, partly related to altered perception of emotions, is commonly reported in Huntington's disease (HD). Aims: To evaluate social cognition in symptomatic HD patients and its possible predictors. Methods: 12 HD patients (stage II S&F, CAG 40.5 ± 2.5) and 9 healthy controls, matched for age and educational level, performed neuropsychological (Montreal Cognitive assessment- MoCa; Mini Mental State Assessment- MMSE; Frontal Assessment Battery- FAB) and social cognition batteries (Faux Pas test, Bush vignettes test, emotion recognition from both faces expression and verbal stimuli, Strange stories test). After 2 years 8 HD patients were re-evaluated through the same tests. Results: HD patients, comparing to controls, showed lower performances in social cognition, particularly in Faux pas test and Strange Stories, and in recognising negative emotions from face expression (KDEF scale) and verbal emotions (p < 0.05, p < 0.01), as well as cognitive impairment expressed by MoCa, MMSE and FAB (p < 0.01). MoCa and MMSE showed positive correlation with social cognitive tests. At the follow up there were no significative differences in motor and cognitive scales (baseline: MoCa 18.6 ± 4.7, MMSE 26.5 ± 2.2, UHDRS 35.2 ± 8.2); (Follow-up: MoCa 19.8 ± 5.6, MMSE 25.5 ± 3.4, UHDRS 36 ± 11.2). Statistical analysis revealed a negative correlation between CAG and Bush vignettes Score (p < 0.05). Moreover, patients with higher MoCa scores at the baseline showed better performances in KDEF total score (p < 0.05), in particular disgust (p < 0.05), and at the strange stories test (p < 0.01); whereas MMSE showed positive correlation only with strange stories test (p < 0.05). Conclusions: The present study, albeit limited by small sample size, confirms an impairment of social cognition in HD; in addition it suggests CAG expansion and cognitive performances (MoCa and MMSE scores) as possible predictors of social cognition impairment in the course of the disease.